Photobiomodulation Therapy in the Management of Burning Mouth Syndrome: Morphological Variations in the Capillary Bed - Giuseppe Alessandro Scardina; Sofia Casella; Giuseppa Bilello; Pietro Messina (MDPI AG, 2020)
Burning mouth syndrome (BMS) is an idiopathic condition that manifests itself primarily with the onset of a burning sensation. The aim of this research was to perform photobiomodulation therapy (PBM) using a diode laser on the oral mucosa of BMS patients, followed by an objective evaluation of the morphological changes in the vascular bed underlying the mucosa using polarized light videocapillaroscopy. A group of 40 patients were included in the study. The patients were randomly divided into two groups (using simple randomization) as follows: 20 patients were assigned to the laser group and 20 patients were assigned to the placebo group. Each patient of the laser group received eight irradiations (with 4 Watt of power, wavelength 800 nm, energy 1200 Joules, irradiation time of 300 s, energy density 50 J/cm2, 60 mW continuous wave laser, and irradiance 180 mW/cm2), twice a week, blinded to the type of irradiation administered, for four consecutive weeks. The patients in the placebo group underwent the same sessions as the other patients, the only difference was the non-emission of the laser. An initial check of the vascular bed was performed with a polarized light videocapillaroscope. This was followed by treatment with a therapeutic diode laser and a subsequent check with a videocapillaroscope. We observed that in the group of patients who underwent laser therapy, there was a lasting improvement in symptoms. The capillary oral bed of patients in the placebo group did not show any statistically significant difference (p > 0.05). In the laser group we observed the following: in the buccal mucosa the diameter of the capillary had a reduction of 3 μm; in the upper lip mucosa, there was a reduction of 3 μm; in the lower lip mucosa, there was a reduction of 3 μm; and in the dorsal lingual surface, there was a reduction of 2 μm. An increase in capillary length was also obtained in all irradiated regions in the laser group patients (p < 0.05). PBM induces microcirculatory changes that are still present over a long period of time, such as an improvement in the clinical picture. The improvement in the symptoms has been correlated to the reduction of the capillary diameter. The placebo effect only led to a temporary improvement in symptoms that were unrelated to changes in the microcirculatory pattern.